Parques eólicos e comunidades tradicionais no Nordeste brasileiro: estudo de caso da Comunidade de Xavier, litoral oeste do Ceará, por meio da abordagem ecológica/participativa - Mendes, Jocicléa de Sousa (2016)
The northeastern coast of Brazil has been occupied gradually by large enterprises, all justified as sources of employment thus improving the quality of life of traditional communities. In Ceará, most part of these enterprises have been located in traditional communities territories, influencing their way of life. In this context, it is inserted the Xavier community, located approximately 347 km from Fortaleza, the state capital. This community is consisted of 20 families who survive from extractive activities like artisanal fishing and shellfish picking besides crop in ebb terrains (lower wetlands formed from dunes near ponds), configured as an essentially traditional community. However, in the midst of the community sustainable living, in 2009, it was inserted about 200 meters from the far eastern of the houses densification, one of the biggest centers of wind farms in Brazil. The insertion of this great enterprise in the area has caused bitter disputes and territorial losses. In this context, the objective of this study was to carry out an integrated analysis of the scenario, especially the socioeconomic dynamic with the community of Xavier beach, through participatory methodologies, focusing on the impacts caused by the installation of the wind farm. The research was based on the Geoecology of Landscapes method that gave support and guidance to achieve the proposed goals. In relation to the methodological aspects of the research, it was used questionnaires, participant observations, techniques of social cartography, application of Q method, field work and construction of maps. The result of the research found that in Xavier beach there are several landscape units: (i) Marine coastal ii) beach and after beach, iv) moving dunes, v) fixed and semi-fixed dunes, vi) eolianites, vii) sprinkling wind plain viii) estuarine plain and ix) coastal, characterized by the integration of various elements that maintains mutual relations with each other and are continuously subjected to flows of matter and energy, as well as the external human action, specifically the construction of the wind project. On the other hand, in social terms, the community is characterized as being essentially traditional and historically without adequate public services (education, health, basic sanitation, public transport and housing), although part of the these services have now been made possible by the compensatory actions of the wind farm. The impacts of the wind farm could be divided into: (a) Positives: access to quality housing and energy; improved school transport and roads leading to the community, all arising as compensatory actions after intense struggle between the local community and the Brazilian Justice; and (b) Negatives: privatization of common areas (dunes and ponds); reduction of surface freshwater supply; suppression of freshwater ponds where it was artisanal fishing; uncomfortable noise from the wind turbines; constant fear of some accident; and internal conflicts, especially after the compensatory actions. Thus, it was concluded that the installation of the wind farm in Xavier community caused essentially negative impacts, affecting expressively the natural elements and the routine of local residents and by having the compensatory actions influenced directly on the acceptance of inhabitants of the wind farm, thereby creating internal conflicts and behavioral changes in individual and collective character. Here are some actions that can contribute to the permanence of the Xavier community territory and ensure the continuation of extractive activities and family agriculture: (i) Strengthening of Residents Association (ii) public investment in artisanal fishing (iii) Creation of a Marine Extractive Reserve (RESEX) in the region.